Experimental and numerical study of the natural convection from a heated horizontal cylinder wrapped with a layer of textile material - Atayilmaz, S. Oezguer; Teke, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Natural convection treat transfer enhancement from a horizontal cylinder with a textile coating is studied experimentally and numerically. The coating layer may be used for two purposes According to the thickness of the coating it may be used as an insulating material or for surface augmentation. In the experimental study. two cylinders having different diameters of 4 8 mill and 9.45 mm are used. The bare cylinders having a radius smaller than a certain critical size were wrapped with a textile material. Wrapped cylinder diameters were increased to 9 and 12.8 mm respectively after coating and constant heat flux was applied to all bare and wrapped cylinders. Experimental study was carried out at different ambient temperatures in a conditioned room which can be maintained at a stable required value and inside a sufficiently designed test cabin The. ambient and cylinder surface temperatures (T-infinity and T-w) varied between 10 degrees C-40 degrees C and 20 C-60 degrees C respectively. Heat transfer rates from bare and wrapped horizontal cylinders were compared and heat transfer enhancement was observed. On the basis of the experimental data average Nusselt numbers were calculated and compared with the well known correlations on natural convection heat transfer from a horizontal cylinder in the specified range of Rayleigh number, and it is seen that the results are in good agreement. The problem is also investigated numerically. Experimental and the numerical results fall in +/- 30% band (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Heat transfer; Horizontal cylinder; CFD; CRITICAL RADIUS; EQUATIONS; CHANNELS; LAMINAR; SURFACE; Thermodynamics; Mechanics